Novel 3-fluoro-6-methoxyquinoline derivatives as inhibitors of bacterial DNA gyrase and topoisomerase IV. Issue 15 (1st August 2017) - Mitton-Fry, Mark J.; Brickner, Steven J.; Hamel, Judith C.; Barham, Rose; Brennan, Lori; Casavant, Jeffrey M.; Ding, Xiaoyuan; Finegan, Steven; Hardink, Joel; Hoang, Thuy; Huband, Michael D.; Maloney, Meghan; et al.
Graphical abstract: Abstract: Novel (non-fluoroquinolone) inhibitors of bacterial type II topoisomerases (NBTIs) are an emerging class of antibacterial agents. We report an optimized series of cyclobutylaryl-substituted NBTIs. Compound14 demonstrated excellent activity both in vitro ( S. aureus MIC90  = 0.125 μg/mL) and in vivo (systemic and tissue infections). Enhanced inhibition of Topoisomerase IV correlated with improved activity in S. aureus strains with mutations conferring resistance to NBTIs. Compound14 also displayed an improved hERG IC50 of 85.9 μM and a favorable profile in the anesthetized guinea pig model.